Students’ perceptions on distance learning: Problems to be solved in the post COVID-19 era - Murakami , Manabu; Jin, Shigeki; Kotaro Matoba (Journal of the Pakistan Medical Association, 2022)
The COVID-19 pandemic has affected medical education worldwide. While some researchers realised the importance of using information technology before the pandemic,1 online education has progressed, and synchronous or asynchronous distant learning has become widely adopted in medical education.2 Accordingly, recent studies have identified factors that promote or inhibit distance learning.3,4 Reinhart et al. interviewed fifth-year German medical students studying clinical medicine. They found that the following five significant factors influenced distance learning: “mental wellbeing,” “communication,” “structure and self-organisation,” “technical issues,” and “learning and commitment.” 3 We felt that the study would be transferable and planned a similar study in a medical school. We interviewed 21 first-year students at Hokkaido University in Japan. We also interviewed 12 third-year and 5 fifth-year students as additional data for reference. The main research question was, “What problems do students face in online education?” With the students’ consent, their interviews were recorded and transcribed. The transcribed scripts were fragmented, codified, and organised into categories. The university ethics committee approved this study (approval number 20-003). Students’ problems were divided into four categories: 1. communication and relationship; 2. content suitability; 3. effects on student life; and 4. technology and network (Table 1). Many parts overlap with the results of the previous study.3 In our research, first year students with weak relationships and fifth-year students enrolled in clinical practice had a negative attitude towards online education. In contrast, third-year students enrolled in medical lectures had a positive attitude. The previous research5 suggested that it is preferable to adopt a blended approach, a combination of distance learning and traditional face-to-face learning, to increase students’ satisfaction and learning outcomes. Our results are consistent with the study mentioned above and suggest that lectures or practice using only distance- learning may be inadequate in medical education outcomes. Memon et al.1 focused on blended learning using learning management systems in Pakistan before the pandemic. Although we don’t know why they had recognised its importance in 2018, we strongly agree that blended learning should be promoted and utilised in medical education, especially since this will become the post-pandemic “new normal.” With the current pandemic afflicting numerous countries, we expect our research to help improve global medical education in the post- COVID-19 era.